Essays on interactive economic behaviors - Xu, Cheng (2021)
This thesis is composed of three projects investigating interactive economic behaviors. Chapter 2 investigates the link between urbanization and interpersonal trust by conducting a field trust game under a natural experiment context. I find that urbanization does not significantly decrease the trust towards co-villagers, meaning the in-group trust did not change statistically significantly. However, the trust towards outsiders does increase as a result of state-led urbanization. I also run a regression on the trust exhibited towards participants in the experiment and found the partial effect of whether they are co-villagers or outsiders weakens as a result of the urbanization, and therefore conclude urbanization decreases out-group discrimination in trust. The second project examines the gender effects on entrepreneurs’ competitiveness and innovative behaviors via a lab-experimental approach. This project finds (i) female participants are less inclined to choose a scheme with an uncertain payoff in an individual-oriented task-solving game whereas (ii) they are as willing as males to choose the scheme in a cooperative-oriented task-solving game. The last project looks into the impacts of humans’ early experiences on ethical behaviors. We found that (i) firms with CEOs who experienced the Great Chinese Famine score lesser in CSR ratings than the comparison group; (ii) this negative relation is more pronounced in firms with CEOs who were younger when they encountered the Great Chinese Famine.